MDP25 mediates the fine‐tuning of microtubule organization in response to salt stress. Issue 6 (27th May 2022) - Yang, Peizhi; Jin, Jingwei; Zhang, Jingru; Wang, Dan; Bai, Xuechun; Xie, Wenfei; Hu, Tianming; Zhao, Xuan; Mao, Tonglin; Qin, Tao
Abstract: Microtubules are dynamic cytoskeleton structures playing fundamental roles in plant responses to salt stress. The precise mechanisms by which microtubule organization is regulated under salt stress are largely unknown. Here, we report that Arabidopsis thaliana MICROTUBULE‐DESTABILIZING PROTEIN 25 (MDP25; also known as PLASMA MEMBRANE‐ASSOCIATED CATION‐BINDING PROTEIN 1 (PCaP1)) helps regulate microtubule organization. Under salt treatment, elevated cytosolic Ca 2+ concentration caused MDP25 to partially dissociate from the plasma membrane, promoting microtubule depolymerization. When Ca 2+ signaling was blocked by BAPTA‐AM or LaCl3, microtubule depolymerization in wild‐type and MDP25 ‐overexpressing cells was slower, while there was no obvious change in mdp25 cells. Knockout of MDP25 improved microtubule reassembly and was conducive to microtubule integrity under long‐term salt treatment and microtubule recovery after salt stress. Moreover, mdp25 seedlings exhibited a higher survival rate under salt stress. The presence microtubule‐disrupting reagent oryzalin or microtubule‐stabilizing reagent paclitaxel differentially affected the survival rates of different genotypes under salt stress. MDP25 promoted microtubule instability by affecting the catastrophe and rescue frequencies, shrinkage rate and time in pause phase at the microtubule plus‐end and the depolymerization rate at the microtubule minus‐end. These findings reveal a role for MDP25 in regulating microtubule organization under salt treatment by affecting microtubule dynamics. Abstract : Arabidopsis MICROTUBULE‐DESTABILIZING PROTEIN 25 decodes the Ca 2+ signal stimulated by salt stress and regulates microtubule organization by affecting the dynamics of individual microtubules at both the plus‐ and minus‐ends.